Challenges for Sensitive Quantification of Gene Editing "Off‐Target" Activity. Issue 1 (25th January 2017) - Tsai, Shengdar Q.
Abstract : Error rates of current high‐throughput sequencing technologies limit quantification of low‐frequency off‐target gene‐editing activity. The principles of gene editing are introduced and discussed, along with current challenges in targeted quantification and validation of low‐frequency gene‐editing off‐target sites and the detection of mutations with regard to improving current sensitivity limits.